Home » Aptitude » Algebra » Question
  1. If xy + yz + zx = 0, then
    1
    +
    1
    +
    1
    (x, y, z ≠ 0) is equal to:
    x2 − yzy2 − zxz2 − xy
    1. 3
    2. 1
    3. x + y + z
    4. 0
Correct Option: D

x2 − yz = x2 − + xy + zx = x (x + y + z)
[∵  xy + yz + zx = 0
⇒  yz = −xy −zx]
Similarly,
y2 − zx = y (x + y + z)
z2 − xy = x (x + y + z)

∴  Expression =
1
+
1
+
1
x(x + y + z)y(x + y + z)z(x + y + z)

=
yz + zx + xy
= 0
xyz(x + y + z)



Your comments will be displayed only after manual approval.